Dietary therapy of functional digestive disorders in children of the first year of life: evaluation of clinical efficacy of a formula containing carob bean gum - G. R. Sagitova; V. M. Sereda; A. I. Danilova; V. A. Shuldais; N. V. Klyueva; I. A. Temerev (Лечащий Врач)
Background. Functional gastrointestinal disorders in the first year of life are a common problem for the child and parents. In addition to significant discomfort for the family, they often lead to a range of inconsistent behaviors that include duplicate consultations with different health care providers, frequent changes in types and names of infant formula, or the use of expensive non-medication treatments. According to current data, 54.9% of infants exhibit at least one symptom of functional gastrointestinal disorders between 0 and 6 months of age. The most common functional digestive disorders of the first 12 months of life include regurgitation, infantile colic and functional constipation.Objective. The purpose of the study was to assess the safety and tolerability of infant formula containing locust bean gum and prebiotics galacto- and fructooligosaccharides (GOS/FOS). The study assessed the effectiveness of the mixture in reducing symptoms of functional disorders of the gastrointestinal tract in children of the first year of life also.Results. This 4-week, open-label, non-randomized, prospective post-registration study enrolled 40 formula-fed or formula-fed infants aged 2 to 14 weeks. The tested formula contained 0.4 g/100 ml locust bean gum as a thickener and 0.4 g/100 ml prebiotics, short-chain galacto-oligosaccharides (scGOS) and long-chain fructo-oligosaccharides (lsFOS) in a 9:1 ratio. Infants receiving locust bean gum and the prebiotics scGOS/lcFOS 9:1 formula demonstrated a significant reduction in the frequency and intensity of symptoms of functional gastrointestinal disorders, including infantile colic (92%) and regurgitation (100%) over 4 weeks of use. The average parental satisfaction with diet therapy was 9 out of 10 points.Conclusion. An infant formula containing locust bean gum and prebiotics scGOS/lcFOS 9:1 is well tolerated and ensures adequate growth. Analysis of the collected data shows that the formula leads to a decrease in functional gastrointestinal disorders, eliminating regurgitation in 100% of children and infant colic in 92% of children by the end of the study.